JSON-BASED PATIENT DATA ARCHITECTURE: A NOVEL APPROACH TO HEALTHCARE INFORMATION STORAGE IN SALESFORCE CRM - Ravi Chandra Chinta, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article presents an innovative approach to healthcare data management within the Salesforce platform, introducing a JSON-based storage architecture utilizing Text Area Long fields for comprehensive patient information. The article examines the implementation of this storage methodology at a healthcare organization, analyzing its effectiveness in managing diverse medical data including laboratory results, diagnostic imaging, procedures, medications, and patient histories. The article demonstrates significant advantages in storage optimization and cost reduction while maintaining robust security protocols and regulatory compliance. The article indicates that this architectural approach not only addresses traditional storage limitations but also enhances data accessibility and maintenance efficiency. The article provides valuable insights into modern healthcare data management strategies, offering a scalable solution for healthcare organizations facing similar challenges in their digital transformation journey. Furthermore, the article explores the security implications and performance metrics of this implementation, contributing to the broader discourse on healthcare information systems optimization.